Thermodynamic analysis of ideal thermocompressor based on Euler view. Issue 1 (1st May 2022) - Wu, S S; Wang, J; Zhang, H C; Huang, C J; Li, L F; Zhou, Y
Abstract: The thermocompressor is the driving source and the core heat-work conversion part of Vuilleumier (VM) refrigerator, which cause pressure fluctuation of the gas by converting the thermal energy at a constant volume. The thermocompressor is consists of cylinder, heater, generator, cooler, displacer, driving mechanism, load, hot cavity and cold cavity. Therefore, the ideal thermocompressor was introduced for thermal analysis to simplify the thermodynamic process and components. In order to better understand the principle of heat-work conversion in the ideal thermocompressor, firstly, the thermodynamic concept of the variable mass system that can be used in the ideal thermocompressor was introduced. Secondly, the thermodynamic process of the ideal thermocompressor under the Euler view was analyzed. Thirdly, the internal operation characteristics of the thermocompressor without load and driving displacer type refrigerator were discussed. At last, the distributions of enthalpy flow, entropy flow and exergy flow in all parts of the ideal thermocompressor were carried out. The results show that the thermocompressor does not output the net entropy flow to the load in one cycle and the flow exergy output by thermocompressor is equal in quantity to the acoustic power output by thermocompressor.